Labour efficiency in Belarus within the framework of achieving sustainable development goals - Kolesnikova, Irina I. (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The labour market in the Republic of Belarus has been recently developing the conditions which have witnessed a constant decrease in the number of people employed in the economy due to the transformation of the population structure. Among the factors that impede the effective development of the regions, uneven territorial distribution of labour potential was revealed. It leads to labour redundancy in some regions and a shortage of personnel in others. The main goal of the study is to investigate the influence of selected factors on labour market indicators in the Republic of Belarus in 2013–2018. The indicators under research characterise standard of living, unemployment, rationality of personnel policy, employment efficiency, labour productivity and others. Thus, it is possible to assess the efficiency of labour potential management in the framework of achieving sustainable development goals. As a research tool, statistical methods were used, including the method of comparisons, the multivariate index models, correlation and regression analysis. The solution to the problem of territorial inequality in the labour market can be found through a number of measures that are aimed at: stimulating labour mobility of citizens; creation of new attractive jobs in labour-intensive areas; assistance in employment and housing; organization of training for the unemployed in professions that are in demand on the regional labour market; simplification of starting business procedures, etc. To ensure sustainable development in the face of a decrease in the number of employees, as well as a decrease in the share of workers, this tendency must be correlated with the processes of improving labour methods and techniques, modernizing production, introducing new equipment and resource-saving technologies, automating production processes to ensure increased labour productivity and reduced excess employment.

W ostatnich latach rynek pracy na Białorusi funkcjonuje w warunkach stałego spadku liczby osób zatrudnionych w gospodarce w wyniku zmiany struktury demograficznej ludności. Dodatkowym problem jest nierównomierny rozkład potencjału siły roboczej między regionami, co prowadzi do zwolnień siły roboczej w niektórych regionach i niedoboru siły roboczej w innych. Głównym celem opracowania jest określenie wpływu wybranych czynników na wskaźniki rynku pracy na Białorusi w latach 2013–2018. Badane wskaźniki charakteryzują poziom życia, bezrobocie, racjonalność polityki personalnej, efektywność zatrudnienia, wydajność pracy i inne. Pozwoliło to na ocenę efektywności zarządzania potencjałem pracy w ramach osiągania celów zrównoważonego rozwoju. Jako narzędzie badawcze zastosowano metody statystyczne, w tym metodę porównań oraz analizę korelacji i regresji. Rozwiązanie problemu nierówności terytorialnych na rynku pracy można osiągnąć za pomocą wielu środków mających na celu: stymulowanie mobilności siły roboczej obywateli; pomoc w zakresie zatrudnienia i zakwaterowania; tworzenie nowych atrakcyjnych miejsc pracy na obszarach bogatych w zasoby pracy; organizację szkoleń dla bezrobotnych w zawodach poszukiwanych na regionalnym rynku pracy; uproszczenia zakładania własnej działalności gospodarczej itp. Aby zapewnić zrównoważony rozwój, w obliczu zmniejszających się zasobów pracy, tendencję tę należy skorelować z procesami doskonalenia metod i technik pracy, modernizacji produkcji, w tym wprowadzania technologii automatyzujących procesy produkcyjne w celu zwiększenia wydajności pracy i zmniejszenia nadwyżki zatrudnienia.
Keywords: economically active; labour force; unemployed; personnel structure efficiency; manageability rate; sustainable development goals; aktywność ekonomiczna; siła robocza; bezrobotni; efektywność struktury zatrudnienia; wskaźnik zarządzania; cele zrównoważonego rozwoju